Advancements in smart wearable patch systems for enhanced wound healing - Samathoti, Prasanthi; Bodagala, Sai Ramya (Creative Pharma Assent, 2025)
Background: Chronic wounds afflict around 2% of the world's population and cost billions of dollars each year in medical costs. By some estimates, over 13 million people worldwide suffer from chronic wounds yearly. The absence of continuous surveillance in conventional dressings for wounds causes prolongation in the treatment and raises the danger of infection. Timely and practical assessment of wounds is key to reducing infection and healing wounds. This is possible by smart dressings with sensors continuously providing input while monitoring important wound variables involving pH, temperature, and moisture. Considering current and upcoming advancements, this paper examines how intelligent patches could transform healing. Methodology: The latest advances in the development, usage of intelligent patches, and their development by different researchers are highlighted in this review. It looks at how sensors are incorporated into these patches and provides an overview of developing intelligent wound dressings by integrating one or more sensors triggered by endogenous and exogenous stimuli. Results and Discussion: The fabrication and effectiveness of intelligent dressings have advanced significantly, but there are still issues with sensor precision and resilience, especially regarding the requirement for strict regulations. The discussion also explores the critical need to address legal and technological constraints to enhance the usefulness of such wearable gadgets in medical settings. Conclusion: Intelligent patches, a fascinating new development in wound care, enable customized therapy with continuous surveillance. Future studies should address real-world challenges to fully realize their potential to refine wound recovery outcomes in medical care.